SINGLE STAGE RF AMPLIFIER AT 5.8GHZ ISM BAND WITH IEEE 802.11a STANDARD - Othman, A. R.; Ibrahim, I. M.; Samingan, M. S. A. S.; Aziz, A. A. A.; Selamat, M. F. M.; Halim, H. C. (2007)
This paper describes the circuit design and measurement of a single stage RF amplifier for 5.8 GHz-band with IEEE 802.11a standards for WLAN applications.The circuit was simulated using Ansoft Designer where a 14dB of gain; input and output return loss less than -10dB were observed. The GaAs Hetrojunction FET (HFET), capacitors and resistors are combined with the microstrip line pattern by silver epoxy. A 1dB output power compression point (P1dB) of 17dBm and 14.56dB of gain when -1dBm power injected under 6V and ½ Idss biasing are measured.